EFFECT OF MINERALS AND ENZYMES SUPPLEMENTATION ON POSTPARTUM FERTILITY AND BLOOD PROFILE OF PROGESTERONE AND METABOLITES IN TRIPLE CROSSBRED COWS - Hadiya, K K; Derashri , H J; Sarvaiya , N P (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
Twenty healthy freshly calved triple crossbred (HF x J x K) cows were divided randomly into four groups each of five animals from the day of calving to observe the effect of supplementation of minerals + proteins vitamins (Nutri-sacc power pack, Vetcare) and enzymes (Neozyme RU, Biocon India Ltd) on postpartum fertility and fortnightly blood plasma profile of hormone progesterone and certain metabolites from calving till 15th week postpartum. The animals of Group-I (T0) served as control; of Group-II (T1) were given nutri sacc powder (@100 g/d/h; while animals of Group–III (T2) and Group IV (T3) received neozyme supplementation @ 750 and 1000 g per ton of concentrate mixture, which was fed @ 1 kg for every 3 kg milk. The supplementation of minerals and enzymes did not influence significantly the intervals of first oestrus postpartum (31±0.60 days) or service period (147±13.69 days). The pooled average plasma progesterone and glucose concentrations were 0.76±0.14 ng/ml and 69.37±2.84 mg %, respectively, with significant (P<0.01) effect of periods, but not of groups. The values for glucose were highest 60 days postpartum. Average plasma total protein (8.87±0.18 g %) varied neither among groups nor among periods. The average plasma levels of cholesterol and triglyceride were 143.37±6.41 and 160.62±9.28 mg %, respectively. These were also not influenced by the groups or periods. The results indicated that supplementation of minerals + protein–vitamins or enzymes at given level during postpartum period were not distinctly beneficial in triple crossbred cows.